Case study: Understanding the formation of squat-type defects in a metropolitan railway. (May 2021) - Bedoya-Zapata, Á.D.; Rojas-Parra, S.; Díaz-Mazo, J.H.; García-Jiménez, J.A.; López-Londoño, J.E.; Vergara-Puello, R.A.; Molina, L.F.; Santa-Marín, J.F.; Toro, A.; Mesaritis, M.; Lewis, R.; Palacio, M.
Highlights: A White-Etching layer was found in the field near the squat-type defects. Several root-causes were identified as responsible for the formation of studs. Introduction of new vehicles is the most important cause. Abstract: Squat-type defects are becoming an increasing issue in rail transportation systems. In this work, a root-cause analysis was carried out to identify the main causes leading to squat formation in a metropolitan railway. Several inspection visits were carried out after the first squat appeared in December 2017 in order to collect evidence from the field. The Corrugation-Analysis Trolley (CAT) was used to perform spectral analysis and a number of rail sections were extracted from critical locations of the railway for laboratory analysis of the microstructure. Four root-causes for squat formation were identified, namely: rail corrugation derived from resonance frequencies induced by vehicle-track dynamic interaction, increase of traffic, problems related to maintenance management and inadequate rail grinding. The analysis of data from the field revealed a clear correlation between the formation of squat-type defects and the presence of a White Etching Layer (WEL) on the surface of the rail, whose formation was shown to be most likely induced during the rail grinding operations as it was verified after a controlled grinding experiment. The increase of traffic over the last 15 years, as well as rail corrugation, which was linked with the introduction of new vehicles to the system, were also considered key factors for squat formation.